Ad libitum drinking prevents dehydration during physical work in the heat when adhering to occupational heat stress recommendations. Issue 3 (3rd July 2022) - Hess, Hayden W.; Tarr, Macie L.; Baker, Tyler B.; Hostler, David; Schlader, Zachary J.
ABSTRACT: Government entities issue recommendations that aim to maintain core temperature below 38.0°C and prevent dehydration [>2% body mass loss] in unacclimated workers exposed to heat. Hydration recommendations suggest drinking 237 mL of a cool sport drink every 15–20 min. This is based on the premise that ad libitum drinking results in dehydration due to inadequate fluid replacement, but this has never been examined in the background of recommendation compliant work in the heat. Therefore, we tested the hypothesis that ad libitum drinking results in >2% body mass loss during heat stress recommendation compliant work. Ten subjects completed four trials consisting of 4 hours of exposure to wet bulb globe temperatures (WBGT) of 24.1 ± 0.3°C (A), 26.6 ± 0.2°C (B), 28.5 ± 0.2°C (C), 29.3 ± 0.6°C (D). Subjects walked on a treadmill and work-rest ratios were prescribed as a function of WBGT [work:rest per hour – A: 60:0, B: 45:15, C: 30:30, D: 15:45] and were provided 237 mL of a cool sport drink every 15 min to drink ad libitum . Mean core temperature was higher in Trial A (37.8 ± 0.4°C; p = 0.03) and Trial B (37.6 ± 0.3°C; p = 0.01) versus Trial D (37.3 ± 0.3°C) but did not differ between the other trials (p ≥ 0.20). Body mass loss (A: −0.9 ± 0.7%, B: −0.7 ± 0.5%, C: −0.3 ± 0.5%, D: −0.4 ± 0.6%) was greater in Trial A compared to Trial D (p = 0.04) and was different from 2% body mass loss in all trials (p ≤ 0.01). Ad libitum drinking during recommendation compliant work in the heat rarely resulted in dehydration. Registered Clinical Trial (NCT04767347)